2019
DOI: 10.3390/en12112044
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Deflecting Hydraulic Fracture with Refracturing Using Extended Finite Element Method

Abstract: Refracturing is a key technology in enhancing the conductivity of fractures from hydraulically-fractured wells. However, the deflecting mechanism of the diverting fracture is still unclear. In this paper, a fully coupled seepage-stress model based on the extended finite element method (XFEM) was developed to realize the deflection mechanism of the refracturing fractures. The modified construction of refracturing was then verified by laboratory experiments. Furthermore, two new deflection angles considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sepehri et al [11][12][13] studied the effect of interference between clusters on fracture pattern by considering fluid loss and fluid distribution among clusters and optimized the cluster spacing in multi fracture expansion. Li et al [14,15] found that the less stress difference causes greater fracture deflection when considering the effect of stress difference on fracture expansion. Li et al [16][17][18] studied the fracture pattern in synchronous fracturing and alternate fracturing by considering the fracturing fluid properties and engineering parameters, and concluded that stress interference is significant in synchronous fracturing.…”
Section: Nomenclature Umentioning
confidence: 99%
“…Sepehri et al [11][12][13] studied the effect of interference between clusters on fracture pattern by considering fluid loss and fluid distribution among clusters and optimized the cluster spacing in multi fracture expansion. Li et al [14,15] found that the less stress difference causes greater fracture deflection when considering the effect of stress difference on fracture expansion. Li et al [16][17][18] studied the fracture pattern in synchronous fracturing and alternate fracturing by considering the fracturing fluid properties and engineering parameters, and concluded that stress interference is significant in synchronous fracturing.…”
Section: Nomenclature Umentioning
confidence: 99%
“…The XFEM can be also used to simulate the deflecting hydraulic fracture with refracturing, and it is concluded that the horizontal stress has obvious influence on re-orientation behavior. 24 However, this method can simulate the mechanical behavior of a single crack well, but it is difficulty to describe multi-cracks problems. 25,26 Thus, a meshless numerical method is required to overcome the deficiencies of the mesh-based method in simulating crack propagation and large deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al 23 investigated the hydraulic‐driven crack propagation behavior through employing a cohesive pore pressure element, and the effect of geologic and fracturing parameters on hydraulic‐driven crack propagation in the layered reservoir was analyzed. The XFEM can be also used to simulate the deflecting hydraulic fracture with refracturing, and it is concluded that the horizontal stress has obvious influence on re‐orientation behavior 24 . However, this method can simulate the mechanical behavior of a single crack well, but it is difficulty to describe multi‐cracks problems 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, investigations of the HF deflecting propagation rules focus on the effects of horizontal in situ stresses differences, fracture initiation azimuth, and disturbance stress on HF deflecting trajectory [3][4][5][6]. However, researches on injection rate-dependent (IRD) HF deflecting propagation are relatively limited [7,8]. The limited studies, conducted by true triaxial physical simulation tests of hydraulic fracturing [8] and extended finite element (XFEM) simulations [7], reveal that the increased injection rates remarkably extend the HF deflecting distance.…”
Section: Introductionmentioning
confidence: 99%
“…However, researches on injection rate-dependent (IRD) HF deflecting propagation are relatively limited [7,8]. The limited studies, conducted by true triaxial physical simulation tests of hydraulic fracturing [8] and extended finite element (XFEM) simulations [7], reveal that the increased injection rates remarkably extend the HF deflecting distance. The above investigation provides references for the effective control of HF deflecting propagation.…”
Section: Introductionmentioning
confidence: 99%